Oxidation of free, peptide and protein tryptophan residues mediated by AAPH-derived free radicals: role of alkoxyl and peroxyl radicals. Issue 63 (16th June 2016) - Fuentes-Lemus, E.; Dorta, E.; Escobar, E.; Aspée, A.; Pino, E.; Abasq, M. L.; Speisky, H.; Silva, E.; Lissi, E.; Davies, M. J.; López-Alarcón, C.
Abstract : When AAPH is employed as a free radical source, at low concentrations of free, peptide and protein Trp residues, the oxidation is mostly induced by alkoxyl radicals. However, at high concentrations, both peroxyl and alkoxyl radicals are involved. Abstract : The oxidation of tryptophan (Trp) residues, mediated by peroxyl radicals (ROO˙), follows a complex mechanism involving free radical intermediates, and short chain reactions. The reactivity of Trp towards ROO˙ should be strongly affected by its inclusion in peptides and proteins. To examine the latter, we investigated (by fluorescence) the kinetic of the consumption of free, peptide- and protein-Trp residues towards AAPH (2, 2′-azobis(2-amidinopropane)dihydrochloride)-derived free radicals. Interestingly, the initial consumption rates ( R i ) were only slightly influenced by the inclusion of Trp in small peptides and proteins (human serum albumin and human superoxide dismutase). Depending on the Trp concentration, the R i versus Trp concentration ([Trp]) plots showed three regions. At low Trp concentrations (1–10 μM), a linear dependence was observed between R i and [Trp]; at intermediate Trp concentrations (10–50 μM), the values of R i were nearly constant; and at high Trp concentrations (50 μM to 1 mM), a slower increase of R i than expected for chain reactions. Similar behavior was detected for all three systems (free Trp, and Trp in peptides and proteins). For the first time we are showing that alkoxyl radicals, formed from self-reaction of ROO˙, are responsible of the Trp oxidation at low concentrations, while at high Trp concentrations, a mixture of peroxyl and alkoxyl radicals are involved in the oxidation of Trp residues.